Відповідь:
x = -1
Пояснення:
t = (x^2 +1)/x, тоді x/(x^2+1) = 1/t
Підставляємо в рівняння:
t + 1/t = -5/2
Позбуваємось знаменника (домножаємо кожний член на 2t)
2 * t^2 + 2 = -5t
2 * t^2 + 5 * t + 2 = 0
D = 25 - 4 * 2 * 2 = 9
t1 = (-5 - 3)/4 = -2
t2 = (-5 + 3)/4 = -1/2
1.
(x^2 + 1)/x = -2
x^2 + 1 = -2 * x
x^2 + 2x + 1 = 0
D = 4 - 4 * 1 = 0
x = -2/2
2.
(x^2 + 1)/x = -1/2
2x^2 + 2 = -x
2x^2 + x + 2 = 0
D = 1 - 4 * 2 * 2 = -15 - розв'язків нема
Відповідь:
x = -1
Пояснення:
t = (x^2 +1)/x, тоді x/(x^2+1) = 1/t
Підставляємо в рівняння:
t + 1/t = -5/2
Позбуваємось знаменника (домножаємо кожний член на 2t)
2 * t^2 + 2 = -5t
2 * t^2 + 5 * t + 2 = 0
D = 25 - 4 * 2 * 2 = 9
t1 = (-5 - 3)/4 = -2
t2 = (-5 + 3)/4 = -1/2
1.
(x^2 + 1)/x = -2
x^2 + 1 = -2 * x
x^2 + 2x + 1 = 0
D = 4 - 4 * 1 = 0
x = -2/2
x = -1
2.
(x^2 + 1)/x = -1/2
2x^2 + 2 = -x
2x^2 + x + 2 = 0
D = 1 - 4 * 2 * 2 = -15 - розв'язків нема